Isoform Switching as a Mechanism of Acquired Resistance to Mutant Isocitrate Dehydrogenase Inhibition - Harding, James J.; Lowery, Maeve A.; Shih, Alan H.; Schvartzman, Juan M.; Hou, Shengqi; Famulare, Christopher; Patel, Minal; Roshal, Mikhail; Do, Richard K.; Zehir, Ahmet; You, Daoqi; Selcuklu, S. Duygu; et al. (Cancer discovery, 2018)
Somatic mutations in cytosolic or mitochondrial isoforms of isocitrate dehydrogenase ( or , respectively) contribute to oncogenesis via production of the metabolite 2-hydroxyglutarate (2HG). Isoform-selective IDH inhibitors suppress 2HG production and induce clinical responses in patients with - and -mutant malignancies. Despite the promising activity of IDH inhibitors, the mechanisms that mediate resistance to IDH inhibition are poorly understood. Here, we describe four clinical cases that identify mutant IDH isoform switching, either from mutant IDH1 to mutant IDH2 or vice versa, as a mechanism of acquired clinical resistance to IDH inhibition in solid and liquid tumors. SIGNIFICANCE: IDH-mutant cancers can develop resistance to isoform-selective IDH inhibition by "isoform switching" from mutant IDH1 to mutant IDH2 or vice versa, thereby restoring 2HG production by the tumor. These findings underscore a role for continued 2HG production in tumor progression and suggest therapeutic strategies to prevent or overcome resistance. .